CONFIGURING BOTH BACKBONE AND LOGICAL NETWORKS OF A RECONFIGURABLE NETWORK WITH LINK FAILURES ALLOWED - SUNG, CHANG SUP; LEE, JONG HYUP (Engineering optimization, 1996)
This paper considers a problem of configuring both backbone and logical networks in a reconfigurable circuit-switched network where links are subject to failures. The objective is to design feasible backbone and logical networks at least cost where the cost includes backbone link capacity expansion cost, lost-call traffic penalty, and hop cost (nodal processing cost). The problem is formulated as a zero-one non-linear mixed integer programming problem, for which a solution procedure is developed by use of a Lagrangean relaxation technique and heuristic methods exploited for improving the lower and upper bounds of any intermediate solution. The solution procedure is tested for its effectiveness with various numerical examples.